Traversing the tightrope: the socio-economic impact of covid-19 & reform of social protection policies in Malaysia - Syed Azman, Syed Marwan Mujahid; Nordin, Ikmal; Ng, Ming Yang (Friedrich-Ebert-Stiftung, 2020)
Executive Summary